Enhanced microscale NMR spectroscopy of low-gyromagnetic ratio nuclei via hydrogen transfer - P. Alsina-Bolívar; J. Casanova (Physical Review Research)
Chemical shifts and J-couplings are fundamental parameters in NMR spectroscopy, they provide structural information about molecules. Extracting these quantities from isotopes such as carbon or nitrogen results in reduced sensitivity due to their low gyromagnetic ratios. In this paper, we present a method for detecting chemical shifts and J-couplings at the microscale in low-gyromagnetic-ratio nuclei using NV centers. By leveraging hydrogen nuclei, we achieve strong coupling with NVs and fast signal emission that aligns with NV coherence times. In addition, the technique is well suited for implementations under high magnetic fields. We demonstrate that our protocol achieves a sensitivity enhancement of more than one order of magnitude for scenarios involving ^{13}C, with even greater improvements for nuclei with lower gyromagnetic ratios.